1991
DOI: 10.1103/physrevb.43.12848
|View full text |Cite
|
Sign up to set email alerts
|

Stability of antipolar fluxons in an infinitely long Josephson junction with shunt loss, surface-impedance loss, and bias current

Abstract: Critical curves for the soliton-antisoliton annihilation on the infinitely long Josephson junction under the perturbation of bias current, shunt loss, and surface-impedance loss are 'obtained by means of the perturbation theory presented by McLaughlin and Scott. It is demonstrated that the presence of the surface-impedance loss severely reduces the stability of antipolar Auxons, especially when the shunt loss and bias current are small. The results are compared with experiment, and good agreement is found in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…It is of importance to investigate analytically the chaotic behavior in this situation, as it has not been fully studied, to our knowledge; this is the objective of this work. Other authors working on this subject [9,10] have found numerically that as far as the chaotic behavior is concerned, there is not much change when a small is included in the equation. For relatively large ; the chaotic motion with term resembles that having a larger term (shunt loss) with ¼ 0: In a recent work, Ustinov and Malomed [11] report the experimental observation of ac driven phase-locked motion of a fluxon at a nonzero average velocity in periodically modulated LJJ.…”
Section: Introductionmentioning
confidence: 99%
“…It is of importance to investigate analytically the chaotic behavior in this situation, as it has not been fully studied, to our knowledge; this is the objective of this work. Other authors working on this subject [9,10] have found numerically that as far as the chaotic behavior is concerned, there is not much change when a small is included in the equation. For relatively large ; the chaotic motion with term resembles that having a larger term (shunt loss) with ¼ 0: In a recent work, Ustinov and Malomed [11] report the experimental observation of ac driven phase-locked motion of a fluxon at a nonzero average velocity in periodically modulated LJJ.…”
Section: Introductionmentioning
confidence: 99%